Penyuluhan dan Motivasi Berwirausaha Pada Siswa/i Sekolah Menengah Atas Negeri 01 Tulung Selapan - Asmanita Asmanita; Rolia Wahasusmiah; Verawati Verawati; Citra Indah; Dewi Sartika (Training & Research Institute - Jeramba Ilmu Sukses, 2022)
Entrepreneurs are people able to see and understand business opportunities and act appropriately to ensure success. Running entrepreneurial activities requires motivation as capital for success in entrepreneurship. Entrepreneurship counselling activities and identification of entrepreneurial motivation in Tulung Selapan 01 State Senior High School students aim to convey knowledge about entrepreneurship and want to know the level of entrepreneurial motivation of Tulung Selapan 01 State High School students. The delivery method use lectures, discussions, and questions and answers. Meanwhile, to find out the level of motivation by giving a motivational entrepreneurship questionnaire. The results of the activity showed that there was high motivation in the students to do entrepreneurship, but on the other hand, the students still felt confused and afraid to start. The role of the family, community, educational institutions, government, and the private sector is needed to help create young entrepreneurs